Hydrogen Production From catalytic reforming of greenhouse gases (CO2 and CH4) Over Neodymiun (III) oxide supported Cobalt catalyst - V. Ayodele Bamidele; Herbert Offor Uchechukwu; Edokpayi Osariemen; Christopher, E. Akhabue; T. Akhihiero Ejiroghene; Chin Kui Cheng (Journal of Applied Sciences and Environmental Management, 2017)
Hydrogen production from CO2 reforming of methane over 20wt%.Co/Nd2O3 has been investigated in a fixed bed stainless steel reactor. The 20wt%.Co/Nd2O3 catalyst was synthesized using wet impregnation method and characterized for thermal stability, textural property, crystallinity, morphology and nature of chemical bonds using techniques such as TGA, XRD, N2 adsorption-desorption, FESEM, EDX and FTIR. The CO2 reforming of methane was performed at feed ratio (CH4:CO2) between 0.1-1 and reaction temperature ranged 973-1023 K. The catalyst displayed good activity towards selectivity and yield of hydrogen as well as CO, a by product. The selectivity and yield of Hydrogen increases with feed ratio and reaction temperature. The 20wt%.Co/Nd2O3 catalyst displayed promising catalytic activity for hydrogen production with the highest yield and selectivity of 32.5% and 17.6% respectively.